2014
DOI: 10.7603/s40930-014-0013-z
|View full text |Cite
|
Sign up to set email alerts
|

Tourism at Risk: A Review of Risk and Perceived Risk in Tourism

Abstract: Since the 9/11 attack in 2001, a number of major tragedies, including the SARS outbreak, the Bali bombings, and the Asian tsunami, have swept the tourism industry across the globe. The impact of these crises was unprecedented and thus, it raises the necessity to review the existing risk literature in tourism. This paper reviews the multi-dimensional concept of risk in tourism by analyzing 46 selected articles following the guidelines of content analysis. The findings are categorized into four broad meaning the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 50 publications
2
82
0
3
Order By: Relevance
“…Most tourism recovery strategies are reactive and generally include government aid packages; which (re)focus on domestic tourism and development of new niche tourism products, as well as cost-cutting measures by the sector as a result of a crisis (Tse et al, 2006;Enz & Taylor, 2002). Finally, destination recovery is highly dependent on the perception of risk, a field that is crucial to understanding what is important for tourists in relation to personal safety and security (Lepp & Gibson, 2003;Reisinger & Mavondo, 2005;Taylor & Toohey, 2007;Williams & Baláz, 2013;Yang & Nair, 2014).…”
Section: Tourism Crisis Managementmentioning
confidence: 99%
“…Most tourism recovery strategies are reactive and generally include government aid packages; which (re)focus on domestic tourism and development of new niche tourism products, as well as cost-cutting measures by the sector as a result of a crisis (Tse et al, 2006;Enz & Taylor, 2002). Finally, destination recovery is highly dependent on the perception of risk, a field that is crucial to understanding what is important for tourists in relation to personal safety and security (Lepp & Gibson, 2003;Reisinger & Mavondo, 2005;Taylor & Toohey, 2007;Williams & Baláz, 2013;Yang & Nair, 2014).…”
Section: Tourism Crisis Managementmentioning
confidence: 99%
“…Considering the relevance and influence of risk on tourists and the industry, a considerable body of tourism risk literature has been developed, especially in the past two decades (Yang & Nair, 2015). Nevertheless, a systematic review of risk literature in tourism is absent, which is indicated in Noel Scott's consolidated list of review papers in tourism posted on 3 March 2015 on TRINET 1 .…”
Section: Problems With Existing Risk Research In Tourismmentioning
confidence: 99%
“…In an extensive review of the risk literature, Yang and Nair (2015) highlight that the effects of risk perception on behavioral intention is one of the main focal points of the selected bibliography. 2 The main conclusion to be drawn from these works is that risk perception has the capacity of inhibiting the travel (Um & Crompton, 1992).…”
Section: Risk Perception On Behavioral Intentionmentioning
confidence: 99%
“…There are many works in the literature that analyze the relation between risk and behavior intention (Yang & Nair, 2015), and between destination image and the latter (Chon, 1990;Pike, 2002). Perpiña, Camprubí and Prats (2017) point out that destination image is not the only variable that determines the tourist's choice, emphasizing the influence of perceived risk.…”
Section: Introductionmentioning
confidence: 99%